Moisture Management Finish on Single and Rib Knit Cotton - IJAZ, Mehreen; SAHAR, Namood -e-; TARIQ, Zohra; FATIMA, Rafia; RASHEED, Zahra; TARIQ, Madeeha; DAR, Hibba Munir (Engineering Transactions, 2023)
The present study aimed to determine the effect of moisture transmission finish on the performance of knitted cotton fabrics in terms of their tensile strength and moisture transmission behavior. Two groups: single and rib-knit cotton fabrics were collected from Nishat Mills Limited. A moisture management finish was applied onto the collected fabrics. The effect of the applied finish was investigated against their moisture transmission behavior by following the AATCC 195-2009 test procedure. The tensile strength was also evaluated with the ASTM D 5035-11 test method. The difference was studied between finished and unfinished samples. It was concluded that the moisture transmission finish has decreased the absorption rate and spreading speed of water through/in treated fabrics as compared to untreated fabrics. Moreover, breaking load and elongation of knitted fabrics in both directions were also improved with the application of finish.